HUBUNGAN STATUS PARITAS DENGAN KEJADIAN PERSALINAN KETUBAN PECAH DINI DI RSUD dr. SOESELO SLAWI KABUPATEN - Natiqotul Fatkhiyah (LPPM Universitas Pekalongan, 2011)
Labor with premature ruptur of membranes is high risk to maternal and infant mortality, Which one of the cause is multiparity. the research’s goal is to know The correlation between parity status with premature rupture of membranes, is the parity status can caused premature ruptur of membranes. This research used discriptive correlation method with cross sectional approach. The sampling technic by purposive random sampling and total sample are 620 from 1.235 total population. The result of research, amount of multiparous mother with premature ruptur of membranes 161 (48.35%) and multiparous mother without premature ruptur of membranes 171 (51.65%). Whereas amount of nulliparous mother with premature ruptur of membranes 146 (50.87%) and nulliparous mother without premature ruptur of membranes 141 (49.13%). After analized by chi square test (X2) and p value with 5 % significance level obtained results X2